Aspek Religi dalam Novel Surga yang Tak Dirindukan Karya Asma Nadia: Kajian Semiotik dan Implementasinya dalam Pembelajaran Sastra di Sma - Rifai, Muhamad Agus, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
The purpose of this study was to describe: (1) siocultural background author of the novel Surga yang tak Dirindukan by Asma Nadia; (2) entanglement between elements of structuralism in novel Surga yang tak Dirindukan by Asma Nadia; (3) religious values using semiotic study of iterature contained in the novel Surga yang tak Dirindukan by Asma Nadia; (4) to describe the implementation of the research results from novel Surga yang tak Dirindukan asmaterials criterion teach in high school. The research method using qualitative descriptive. The source of data in this research is the novel Surga yang tak Dirindukan by Asma Nadia. The forms of data in this study a phrases, sentences, or paragraph that contains religious values. The technique of collecting data used the preferences techniques. Data were analyze technique using the method of reading semiotic models that include reading heuristik and hermeunetik. The results of indicate that: (1) sociocultural background of the author of the novel Surga yang tak Dirindukan by Asma Nadia; (2) the elements of structuralism and the fact that the theme of the story has a very strong entanglement and coheren; (3) religious values using semiotic studies contained in the novel Surga yang tak Dirindukan by Asma Nadia; (4) implementation of research results from novel Surga yang tak Dirindukan materials criterion teach in high school. Keywords: religious values, novel Surga yang tak Dirindukan, semiotic, learning literature of high school.